Genes Linking Mitochondrial Function, Cognitive Impairment and Depression are Associated with Endophenotypes Serving Precision Medicine. (1st February 2018) - Petschner, Peter; Gonda, Xenia; Baksa, Daniel; Eszlari, Nora; Trivaks, Michael; Juhasz, Gabriella; Bagdy, Gyorgy
Highlights: Mitochondrial dysfunctions are involved in depression and cognition. MtDNA and nuclear mutations may contribute to depression and cognitive performance. Different combinations of mutations may result in different symptomatology. Better characterization of endophenotypes would advance therapy of this comorbidity. Abstract: Mitochondria densely populate cells in central nervous system providing essential energy for neurons and influencing synaptic plasticity. Harm to these organelles can impair cognitive performance through damaged neurotransmission and altered Ca 2+ homeostasis. Impaired cognition could be one underlying factor which can characterize major depressive disorder, a huge burden for society marked by depressed mood and anhedonia. A growing body of evidence binds mitochondrial dysfunctions with the disease. Cognitive disturbances with different severity are also observable in several patients, suggesting that damage or inherited alterations of mitochondria may have an important role in depression. Since several different biological and environmental factors can lead to depression, mitochondrial changes may represent a significant subgroup of depressive patients although cognitive correlates can remain undiscovered without a specific focus. Hypothesis driven studies instead of GWAS can pinpoint targets relevant only in a subset of depressed population. This review highlights results mainly from candidate gene studies on nuclear DNA of mitochondrion-related proteins, including TOMM40, MTHFD1L, ATP6V1B2 and MAO genes, also implicated in Alzheimer's disease, and alterations in the mitochondrial genome to argue for endophenotypes where impaired mitochondrial function may be the leading cause for depressive symptomatology and parallel cognitive dysfunction.